Espaço-Performativo. Estudos para uma definição - Teresa Rodrigues Monteiro Aguiar (2010)
Man is permanently related to space. The interacti on between them both is intensifi ed through constructi on/by the setti ng up of many items that multi ply its eff ect. The user, as a performer, triggers new experiences in space that provide room for acti on, as well as for thinking and refl ecti ng, a basis to project his/her own wishes and needs. Simultaneously, due to its own characteristi cs, the space, as a place for performing, leads to interacti on, making us act and not just stand. The architectural performance becomes then the experience of space reinforced by a living and reciprocal interacti on between people and their inhabited space. The performing space is thus a space for parti cipati ng in which the commitment of senses takes place.